Extending UTAUT2 with Perceived Risk and Trust: Evidence from Digital Banking Adoption in the Kurdistan Region of Iraq - Aridah, Mamoun Walid; Ramadhan, Sherzad; Ahmed, Fareeba; Khorsheed, Hariwan; Obaied, Shamal; Aldulaimi, Amar (European Scientific Journal, ESJ, 2026)
Purpose: This research extends the Unified Theory of Acceptance and Use of Technology (UTAUT2) to investigate the variables affecting the adoption and use of digital banking services. In fragile economic environments, particular attention is paid to the negative impacts of perceived risk and the functions of trust as a direct predictor and modifier of behavioral intention to use digital banking. Design/methodology/approach: A cross-sectional study was conducted with 360 users of digital banking services in the Kurdistan Region of Iraq. Structural Equation Modeling using SmartPLS 4 was used to evaluate the proposed correlations. Principal structural model evaluations included path coefficients, R², Q², f² effect sizes, and collinearity diagnostics. The model’s predictive efficacy was assessed with PLSpredict, contrasting PLS-SEM with linear regression and naïve standards. Findings: The findings indicate that performance expectation, effort expectancy, social influence, facilitating conditions, and trust have a large positive impact on behavioral intention; however, perceived risk has a significant negative effect. Behavioral intention is a robust predictor of consumption behavior. Trust favorably affects behavioral intention but does not substantially attenuate the adverse link between perceived risk and behavioral intention. The model exhibits sufficient explanatory power (R² = 0.440 for BI; R² = 0.409 for UB) and moderate predictive capabilities for essential markers. Originality/value: This research enhances the digital banking adoption literature by integrating UTAUT2 with perceived risk and trust in a high-risk, undeveloped economic context. It offers empirical insights into the influence of psychological and environmental aspects on user behavior in volatile markets. The results provide actionable insights for financial institutions seeking to develop safe, trust-building digital platforms that reduce risk perception and bolster user confidence.